2019
DOI: 10.1155/2019/1491796
|View full text |Cite
|
Sign up to set email alerts
|

Modified Percutaneous Achilles Tendon Lengthening by Triple Hemisection for Achilles Tendon Contracture

Abstract: Background Both percutaneous Achilles tendon lengthening by triple hemisection and the traditional open Z-lengthening are effective methods for Achilles tendon contracture. This study aims to evaluate the efficacy and safety of this new therapeutic method, which is based on the percutaneous sliding technique with three hemi-cuts in the tendon, as compared with the traditional open Z-lengthening. Methods Retrospective analysis of the Achilles tendon contracture cases in our hospital between January 2010 and Sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 27 publications
0
14
0
2
Order By: Relevance
“…In the first surgical treatment of simple Achilles tendon contracture, satisfactory results have been achieved with the application of triple hemisection percutaneous Achilles tendon lengthening 10 , 11 . As a new technique, it has the following four characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the first surgical treatment of simple Achilles tendon contracture, satisfactory results have been achieved with the application of triple hemisection percutaneous Achilles tendon lengthening 10 , 11 . As a new technique, it has the following four characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of Achilles tendon lengthening is to improve the dorsiflexion of the ankle joint and correct the deformity. The study of Lin et al 10,11 showed that modified percutaneous Achilles tendon lengthening by triple hemisection was better compared with the traditional open Zlengthening in terms of operation time, tendon healing and incidence of complications. This is because percutaneous lengthening significantly improved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have demonstrated that the percutaneous triple Hoke hemi-section when compared with traditional open Z lengthening approach has approximately onethird of intraoperative time, fewer complications, and no statistically significant differences in therapeutic effect versus open techniques [28]. This method helps to maintain muscle strength and preserve function relative to traditional open Achilles' tendon lengthening procedures and minimizes risk of over lengthening.…”
Section: Authors Preferred Surgical Approach: the Modified Percutaneous Triple Hoke Hemi-section Of The Achilles' Tendonmentioning
confidence: 99%
“…Various operative methods such as arthroereisis, lateral column lengthening osteotomy, calcaneal medial displacement osteotomy, calcaneal-cuboid-cuneiform osteotomy, and arthrodesis can be considered to treat planovalgus foot deformity [ 3 5 , 8 , 10 14 ]. If ATC is present, tendo-Achilles lengthening (TAL) should be performed concomitantly with the planovalgus foot surgery [ 15 17 ].…”
Section: Introductionmentioning
confidence: 99%